Development of a Novel Parasitic-Type Piezoelectric Actuator - Li, Jianping; Zhou, Xiaoqin; Zhao, Hongwei; Shao, Mingkun; Li, Ning; Zhang, Shizhong; Du, Yumeng (IEEE/ASME transactions on mechatronics, 2017)
A piezoelectric actuator based on parasitic motion principle is proposed and tested. The piezoelectric actuator is explored to simultaneously realize coarse (long stroke) and fine (high accuracy) motions using dual-servo control method. The working principle of the proposed piezoelectric actuator is discussed, and finite-element method is adopted. A dynamic model of parasitic motion based on the LuGre friction model is simulated using matlab/Simulink. A prototype is manufactured to investigate working performance. Experimental results indicate that the maximum speed of the presented parasitic-type piezoelectric actuator is 7.95 mm/s and the resolution is 10 nm. These findings confirm the feasibility of the dual-servo nanopositioning system using piezoelectric stacks and flexure hinges.